Mitigation of Optical Interference Noise by Optical Carrier Cancelation in Self-Coherent Reflective PON Uplink Transmission - Soo-Min Kang; Kyoung-Hak Mun; Sang-Min Jung; Sang-Kook Han (IEEE Photonics Journal)
Optical interference noise (OIN), including optical beating interference and Rayleigh back-scattering noise, severely degrades transmission performance in self-coherent reflective passive optical network uplink transmission systems. A simple, cost-effective, and optical interferometry-based optical carrier cancelation method is proposed to reduce OIN. In this experiment, we demonstrate the cancelation of optical carriers, which is a major cause of OIN, up to 29 dB. Under the conditions of higher fiber input power and longer transmission distance, a remarkable improvement in transmission performance in terms of the eye-pattern and bit-error-rate was achieved.